Second language reading of adolescent ELLS: A study of response to retrospective miscue analysis, error coding methodology and transfer of L1 decoding skills in L2 reading - Latham Keh, Melissa Anne (ProQuest Dissertations & Theses, 2014)
It is well documented that ELLs face significant challenges as they develop literacy skills in their second language (NCES, 2007, 2011). This population is diverse and growing rapidly in Massachusetts and across the nation (Massachusetts Department of Elementary and Secondary Education, 2013; NCELA, 2011; Orosco, De Schonewise, De Onis, Klingner, & Hoover, 2008). Yet, this population is often left out of reading studies because of the range of variables they present (Klingner, 2010). This research focuses on the effects of a reading approach on adolescent ELLs, the power of coding systems to capture ELLs' reading errors and how exposure to a second writing system develops metalinguistic skills. In the first study of this dissertation, I examine the effects of an approach called Retrospective Miscue Analysis (RMA; Goodman & Marek, 1996) on six subjects in a school setting, using an n-of-one design to evaluate changes in their reading attributable to RMA. RMA has been researched with diverse learners in case studies; however, data had not been collected to demonstrate whether it could change subjects' fluency or reading comprehension in addition to their attitudes about reading and themselves as readers. My results suggest that students had positive feelings about RMA and believed that they had learned new ways to read, but the results do not point to immediate changes in their decoding accuracy, reading comprehension or fluency with RMA. This approach may have latent effects on overall reading performance by increasing motivation and self-confidence, but it did not appear to have immediate effects on my subjects' reading performance. The second study of this dissertation provides a methodological exploration of two coding systems. The first coding system, Reading Miscue Inventory (RMI; Goodman, Watson, & Burke, 2005) originated in miscue analysis research. The second coding system was developed by Cheng and Caldwell-Harris (to appear) to code oral reading errors Chinese readers made when reading Chinese, and it was also used by the researchers to code native English speakers' oral reading errors. Interview data from RMA was used as an additional lens for understanding the power of coding systems to reveal information about reading miscues, or oral reading errors. The results indicate that RMI needs revision for use with English language learners (ELLs), especially in the Meaning Construction category, but RMI also reminds us to consider miscues within the context of connected text. Cheng and Caldwell-Harris' system, on the other hand, appears to accurately illuminate general relationships between a target word and a reader's error but is limited to word-level analysis of oral reading errors. The third study of this dissertation examined patterns of oral reading errors according to ELLs' first language (L1) background to explore how L1 reading experiences affect the metalinguistic skills second language (L2) readers bring to reading in their L2. Statistical analysis of real word versus nonword oral reading errors subjects made revealed distinct patterns in L2 readers who had learned to read in Chinese versus Cyrillic writing systems. I argue that this difference in errors made by Chinese and Cyrillic readers supports Koda's (2009) Transfer Facilitation Model, which states that metalinguistic awareness reflects the systematic differences in writing systems readers become accustomed to. This difference in errors also appears to contradict predictions that transfer is less operable across unalike orthographies. I also explore Koda's (2009) hypothesis that experience reading a L2 should lead to changes in metalinguistic skills over time. My findings suggest that experienced L2 readers' decoding skills may not change, or may take significant time to change, with exposure to a second writing system.